(untitled) (Journal of the College of Basic Education, 2023)
Found rapprochement between individuals and groups long ago. As a person tends to merge with his peers for the continuity of his life and to exchange feelings and opinions with them, so communication was the basis of interaction and a means of influencing and being affected. It took many forms, from personal communication to mass communication. Public opinion is one of the aspects of communication in its comprehensive sense. It works to shape people’s attitudes and inclinations, and seeks the cohesion and harmony of society on issues affecting its interests and progress.And since the means of mass communication are tools that contribute to building public opinion. The interdependence remained continuous between the two parties and takes cohesion day after day. This research comes to indicate an aspect of that interdependence.After the events of April 4, 2003, local newspapers appeared in Iraq with various characteristics and sects. The changes in the political arena contributed to its emergence, to deal with the affairs of the new life, especially after the abolition of the media institutions that were operating before those events.